Virtual Reality in Waste Management: Evaluating Its Impact on Community Classification Behavior - Peng, Guinong; Leong, Wai Yie (INTI International University, 2024)
The purpose of this study is to explore the impact of virtual reality (VR) technology on improving community garbage sorting behavior through a questionnaire survey. Targeting residents of varying ages, educational backgrounds, and lengths of residence in the community, the study utilized VR technology for garbage classification education and behavior guidance. This comprehensive method evaluated improvements in individuals' willingness, cognition, and practices regarding garbage classification. We designed a multi-dimensional questionnaire and employed a random sampling method to select residents who met specific classification criteria as survey subjects. The research involved analyzing the influence of VR technology on enhancing garbage classification cognition across different demographics, exploring how VR can shift attitudes and willingness towards garbage classification, and investigating its role in promoting actual sorting behavior and frequency. Methodologically, we implemented an immersive VR experience that simulated various types of garbage and classification scenarios, followed by preand post-intervention surveys to measure changes in cognition and behavior. Additionally, we examined the interrelationship between VR technology and other influencing factors, such as policy advocacy, educational background, and community environment. The findings indicate that VR technology significantly enhances residents' understanding of garbage classification standards and improves classification accuracy. Furthermore, the visual representation of the negative environmental impacts of garbage, depicted through VR, profoundly heightened residents' environmental awareness and willingness to engage in garbage classification. This study confirms the practical application value and significant impact of VR technology in improving community garbage sorting behavior, providing a scientific basis for its further promotion and application in community waste management practices.